2023
DOI: 10.1021/acssuschemeng.2c07012
|View full text |Cite
|
Sign up to set email alerts
|

Creating Pores in Chitosan-Derived Humins via in Situ CO2 Formation

Abstract: Converting chitosan-derived humins into nitrogen-doped porous carbon (NPC) is a promising approach to the valorization of humins owing to their inherent nitrogen-containing advantage. Herein, we report the first example of NPC made from chitosan-derived humins, whereby a novel method to fabricate porous humins from chitosan by in situ CO2 strategy was demonstrated. By means of GPC, FT-IR, XPS, and TEM, the formation mechanism of chitosan-derived humins by catalysis of weak acids was proposed via oligomer mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Shen et al explored the HMF-derived humins generation mechanism and revealed that several elementary reactions such as esterification, etherification, acetalization, and aldol condensation were involved . In recent research, Hou et al transformed chitosan-derived humins to nitrogen-doped porous carbon (NPC) through the in situ CO 2 approach . Herein, we have conducted an in-depth exploration of xylose-derived humins and illustrated their structural evolution process, with the mysterious intermediate captured for the first time.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Shen et al explored the HMF-derived humins generation mechanism and revealed that several elementary reactions such as esterification, etherification, acetalization, and aldol condensation were involved . In recent research, Hou et al transformed chitosan-derived humins to nitrogen-doped porous carbon (NPC) through the in situ CO 2 approach . Herein, we have conducted an in-depth exploration of xylose-derived humins and illustrated their structural evolution process, with the mysterious intermediate captured for the first time.…”
Section: Introductionmentioning
confidence: 94%
“…46 In recent research, Hou et al transformed chitosan-derived humins to nitrogen-doped porous carbon (NPC) through the in situ CO 2 approach. 47 Herein, we have conducted an in-depth exploration of xylosederived humins and illustrated their structural evolution process, with the mysterious intermediate captured for the first time.…”
Section: ■ Introductionmentioning
confidence: 99%